PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGINTEGRASIKAN NILAI PROFETIK, TRANSFORMASIONAL, VISIONER, DAN TRANSAKSIONAL PADA IMPLEMENTASI KURIKULUM MERDEKA DI LEMBAGA PENDIDIKAN ISLAM - Hariyadi, Mochamad; Manshur, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of school principals’ leadership in integrating prophetic, transformational, visionary, and transactional values in the implementation of the Merdeka Curriculum in Islamic educational institutions. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving school principals and teachers as key informants. Data analysis used an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the principal’s leadership is integrative and contextual. Prophetic leadership values serve as the moral foundation in building school ethics and culture, while transformational leadership encourages innovation and change, visionary leadership provides strategic direction, and transactional leadership maintains organizational stability through control and reward systems. The integration of these four leadership models has proven to support the successful implementation of the Merdeka Curriculum, as indicated by improved teacher performance, the establishment of a positive school culture, and the development of more innovative and student-centered learning. This study proposes an “Integrative Islamic Leadership” model as a holistic approach to leadership in Islamic education. This model is expected to contribute conceptually to the development of adaptive and relevant educational leadership in the modern era.